Prediction of nodal staging in breast cancer patients with 1-2 sentinel nodes in the Z0011 era. Issue 35 (28th August 2020) - Corsi, Fabio; Sorrentino, Luca; Albasini, Sara; Bossi, Daniela; Morasso, Carlo; Villani, Laura; Truffi, Marta
Abstract : Abstract: The aim of this study was to provide an innovative nomogram to predict the risk of >2 positive nodes in patients fulfilling the Z0011 criteria with 1-2 sentinel lymph nodes (SLNs) only retrieved. From 2007 to 2017, at the Breast Unit of ICS Maugeri Hospital 271 patients with 1-2 macrometastatic SLNs, fulfilling the Z0011 criteria, underwent axillary dissection and were retrospectively reviewed. A mean of 1.5 SLNs per patient were identified and retrieved. One hundred eighty-seven (69.0%) had 1-2 positive nodes, and 84 (31.0%) had >2 metastatic nodes. Independent predictors of axillary status were: positive SLNs/retrieved SLNs ratio (odds ratio [OR] 10.95, P  = .001), extranodal extension (OR 5.51, P  = .0002), and multifocal disease (OR 2.9, P  = .003). A nomogram based on these variables was constructed (area under curve after bootstrap = 0.74). The proposed nomogram might select those patients fulfilling the Z0011 criteria, with 1-2 SLNs harvested, in whom a high axillary tumor burden is expected, aiding to guide adjuvant treatments. Abstract : Supplemental Digital Content is available in the text